2023
DOI: 10.3390/antiox12040914
|View full text |Cite
|
Sign up to set email alerts
|

Rehmannia glutinosa Polysaccharides: Optimization of the Decolorization Process and Antioxidant and Anti-Inflammatory Effects in LPS-Stimulated Porcine Intestinal Epithelial Cells

Abstract: Polysaccharide decolorization has a major effect on polysaccharide function. In the present study, the decolorization of Rehmannia glutinosa polysaccharides (RGP) is optimized using two methods—the AB-8 macroporous resin (RGP-1) method and the H2O2 (RGP-2) method. The optimal decolorization parameters for the AB-8 macroporous resin method were as follows: temperature, 50 °C; macroporous resin addition, 8.4%; decolorization duration, 64 min; and pH, 5. Under these conditions, the overall score was 65.29 ± 3.4%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…[Orobanchaceae; Radix Rehmannia (Sheng-Di-Huang), esteemed for its capacity to purge pathogenic heat from blood and enrich Yin per Chinese medical doctrine ( Zhang et al, 2008 ), is prevalent in many SLE prescriptions like Liu-Wei-Di-Huang-Wan and Zhi-Bai-Di-Huang-Wan ( Ma et al, 2016 ; Chang et al, 2017 ). Its primary active element has proven to activate the Nrf2/Keap1 route and suppress pro-inflammatory factor expression, thus assuming dual roles as anti-inflammatory and antioxidant agents ( Ren et al, 2023 ). Sheng-Di-Huang’s ( Rehmannia glutinosa (Gaertn.)…”
Section: Discussionmentioning
confidence: 99%
“…[Orobanchaceae; Radix Rehmannia (Sheng-Di-Huang), esteemed for its capacity to purge pathogenic heat from blood and enrich Yin per Chinese medical doctrine ( Zhang et al, 2008 ), is prevalent in many SLE prescriptions like Liu-Wei-Di-Huang-Wan and Zhi-Bai-Di-Huang-Wan ( Ma et al, 2016 ; Chang et al, 2017 ). Its primary active element has proven to activate the Nrf2/Keap1 route and suppress pro-inflammatory factor expression, thus assuming dual roles as anti-inflammatory and antioxidant agents ( Ren et al, 2023 ). Sheng-Di-Huang’s ( Rehmannia glutinosa (Gaertn.)…”
Section: Discussionmentioning
confidence: 99%
“…The binding of LPS to Toll-like receptor 4 (TLR4) triggers an inflammatory response ( Ren et al, 2023 ; Tongaonkar et al, 2023 ). One study showed that exposure to LPS activated the TLR4 signaling pathway and microglia in pregnant mice and led to autism-like behavior in the offspring ( Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rehmannia glutinosa, a commonly used herb in traditional Chinese and Korean medicine, has been extensively employed for its therapeutic properties in treating a range of conditions such as inflammation [ 25 ], diabetes [ 26 ], and lipid metabolism disorders [ 27 ]. Within the roots of Rehmannia glutinosa, there is an abundant presence of a compound called Ajugol, an iridoid glycoside known for its antioxidant and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%